Crystal structure of (Z)-3-(1,3-benzodioxol-5-yl)-3-chloro-1-[2,4-di(benzyloxy)-6-hydroxyphenyl]-2- propen-1-one, C30H23ClO6 - Kerr, P.J. (2014)
Zeitschrift fur Kristallographie - New Crystal Structures